Studi Kritis atas Qur’an: A Reformist Translation - Lukman, Fadhli (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
change-newline"> One of some translation works on the Qur’an appears to be eccentric concidering that it reveals some important revisions to traditionaltranslation. This translation is written by Edip Yuksel, Layth Salehal-Shaiban, dan Martha Schulte-Nafeh entittled Qur’an: A ReformistTranslation. This article attempts to question the view of the writers ofQur’an: A Reformist Translation on historicity related to the Qur’an,framed with hermeneutical theory of Gadamer. The article ends to someconclussions that on their view, the Qur’an is a self-suffiient scripture, andtherefore one has no need to seek the extra-Qur’anic aspect. Eventhoughthe writers deny the importance of historicity of the Qur’an, they indeeddepend on the contemporary history which triggers their will to translatethe Qur’an. As they deny the horizons of the text and rely on their owncontemporary horizons, their approach then belongs to subjectivisthermeneutics.